O PRONERA no estado da Paraíba (1998-2008): avanços e limites João Pessoa 2012 - Costa, Dalva Maiza Medeiros (2012)
NATIONAL EDUCATION PROGRAM IN LAND REFORM (PRONERA) is a Federal Government policy, aimed at promoting the education of workers (the) rural, raising the educational level of young people and adults included in agrarian reform settlements. Since its creation in 1988 until the year 2008, when it completed its first decade, PRONERA had served about 470,000 students (as) in Brazil. In the state of Paraiba, until this year, the PRONERA served about 6,701 students and students through 18 courses at various levels, methods and areas of knowledge. This line of study in Popular Education, the Graduate Program in Education at the Federal University of Paraíba (UFPB), cast a look on the role of PRONERA in the first ten years in the state of Paraiba, its progress and identifying limits through, especially the reconstruction of the experiences of participants in the program (the course coordinators, representatives of social movements partners and guarantors of the INCRA). In the first phase of work, we make a documentary and bibliographical research on rural education policies in order to identify the major differential PRONERA: his being the result of the demands of social movements in favor of the construction of an educational proposal for specific the field, ie, bind their courses to the practical and theoretical reflections on the Field of Education. The methodological procedures used were mainly the analysis of documents produced, as the Operations Manual PRONERA, minutes of meetings and reports of projects and courses. During the construction process, we identified the need to listen to some participants and for this reason, we use also the interviews in search of some reports that give us a vision of the Flagship Program. In spite of its many limitations to be overcome at the national level, as the shift in fundingfrom the above in this work, we can say that PRONERA is undeniably relevant in the construction of rural education in our state, constitute an important mechanism of access to education to people of the field, boosting learning and collaborating with local and regional development, from the settlements.